Lyapunov-based synchronization of two coupled chaotic Hindmarsh-Rose neurons - Nguyen, Le Hoa; Hong, Keum-Shik (Journal of Computer Science and Cybernetics, 2014)
This paper addresses the synchronization of coupled chaotic Hindmarsh-Rose neurons. A sufficient condition for self-synchronization is first attained by using Lyapunov method. Also, to achieve the synchronization between two coupled Hindmarsh-Rose neurons when the self-synchronization condition not satisfied, a Lyapunov-based nonlinear control law is proposed and its asymptotic stability is proved. To verify the effectiveness of the proposed method, numerical simulations are performed.